Combination of Ni-Silica Metal (Ni/SiO2 ) from Rice Husk as Heat-Resistant Coating Material for Wall Paint - Putri Yanita Sidabutar; Dafit Ericson Sihotang; Lisnawaty Simatupang (Indonesian Journal of Chemical Science and Technology (IJCST), 2025)
Combination of Silica with Ni to become Ni/SiO2. This study aims to determine the combination of Ni/SiO2 additives to wall paint as a heat-resistant coating material. The characterization used is FTIR and XRD. The initial stage of this study involved the synthesis of nickel silica, after which it was mixed into 10 mL of paint with variations in the addition of nickel silica of 0.1; 0.2; 0.3; 0.4; and 0.5 grams. After that it was tested for heat absorption. Based on the FTIR results on silica, it shows silanol groups (Si-OH) and siloxane groups (Si-O-Si) and the XRD results show that the structure of the resulting silica is amorphous. variations in the mixture of these materials affect the specific heat of the coating. The more Ni/SiO2 that is mixed, the smaller the specific heat will be. This indicates that the coating does not absorb heat but reflects heat.